Effects of Vitamin D3 and Meso-Zeaxanthin on Human Retinal Pigmented Epithelial Cells in Three Integrated in vitro Paradigms of Age-Related Macular Degeneration - Lazzara, Francesca; Conti, Federica; Platania, Chiara Bianca Maria; Eandi, Chiara M.; Drago, Filippo; Bucolo, Claudio (Frontiers in Pharmacology, 2021)
Age related macular degeneration (AMD) is a degenerative retinal disease and one of major causes of irreversible vision loss. AMD has been linked to several pathological factors, such as oxidative stress and inflammation. Moreover, Aβ (1-42) oligomers have been found in drusen, the extracellular deposits that accumulate beneath the retinal pigmented epithelium in AMD patients. Hereby, we investigated the hypothesis that treatment with 1,25(OH)2D3 (vitamin D3) and meso-zeaxathin, physiologically present in the eye, would counteract the toxic effects of three different insults on immortalized human retinal pigmented epithelial cells (ARPE-19). Specifically, ARPE-19 cells have been challenged with Aβ (1-42) oligomers, H2O2, LPS, and TNF-α, respectively. In the present study, we demonstrated that the combination of 1,25(OH)2D3 and meso-zeaxanthin significantly counteracted the cell damage induced by the three insults, at least in these in vitro integrated paradigms of AMD. These results suggest that combination of 1,25(OH)2D3 and meso-zeaxathin could be a useful approach to contrast pathological features of AMD, such as retinal inflammation and oxidative stress.